2008
DOI: 10.1242/jeb.011205
|View full text |Cite
|
Sign up to set email alerts
|

Hematological changes associated with egg production: estrogen dependence and repeatability

Abstract: SUMMARYThe ʻcost of reproductionʼ (i.e. the trade-off between current reproduction and future fecundity and/or survival) is a central concept in life history theory, yet we still know very little about the physiological mechanisms underlying such costs. Recently it has been recognized that reproduction itself or the regulatory (hormonal) mechanisms underlying reproduction might result in ʻcostsʼ (cf. resource-allocation based mechanisms). As one example, it has been suggested that the decrease in hematocrit ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 66 publications
6
38
1
Order By: Relevance
“…Inconsistencies between the two analyses can be attributed to differences in sample size (i.e. not all individuals were included in the diet quality experiment) as well as the significant degree of intraindividual variation in hematological traits typical of this population (see Wagner et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Inconsistencies between the two analyses can be attributed to differences in sample size (i.e. not all individuals were included in the diet quality experiment) as well as the significant degree of intraindividual variation in hematological traits typical of this population (see Wagner et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…A reduction in hematocrit during egg production has been reported in numerous avian species (reviewed by Williams et al, 2004a;Wagner et al, 2008), ranging from -1.5% in the great tit (Horak et al, 1998a) to -10% in the red-billed quelea (Jones, 1983) relative to pre-breeding levels. Furthermore, Kalmbach et al (Kalmbach et al, 2004) concluded that the extent of anemia was proportional to egg laying effort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While there is no information on the effects of E2 on erythropoiesis in fish, estradiol benzoate slowed the maturation of new red blood cells in channel catfish [21]. Elevated E2 in birds caused hemodilution by increasing plasma osmolality due to production of yolk precursors in the liver and their release to the blood, resulting in water movement into the blood to compensate [67]. Plasma vitellogenin levels are often increased in fish following E2 exposure [65], suggesting that, as in birds, hemodilution may also occur in fish.…”
Section: Discussionmentioning
confidence: 99%